PENGAWASAN LEMBAGA OMBUDSMAN RI PERWAKILAN PROVINSI LAMPUNG DALAM PENINGKATAN PELAYANAN PUBLIK DI KOTA BANDAR LAMPUNG - Muhammad Gilang Ramanov; Ida Farida (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
The Ombudsman Institution is a supervisory agency for service public providers organized bystate and government administrators in order to prevent and eliminate the abuse of authority of stateand governance officials in Indonesia and in Lampung Province, especially in Bandar LampungCity. In supervising public services in Bandar Lampung City, researchers saw 175 public reports ofalleged maladministration in 2021, namely 65 unresolved reports which resulted in the workload ofthe Lampung Province RepresentativeOmbudsman Institution. So the problem of this research is: 1. How the supervision of the RI Ombudsman representative of Lampung Provincein public services in Bandar Lampung City? 2. What are the biting and support factors was theIndonesian Ombudsman institution representing Lampung Province follows up onincoming reports on public services in Bandar Lampung City? This research is a descriptivequalitative method with a sociological juridical approach (socio-legal approach). The method isthe interview method, and the documentation obtained is analyzed carefully. The results of fieldresearch show that the supervision of the RI Ombudsman Institution representing Lampung Province inoverseeing public services in Bandar Lampung City has been running as regulated by the centralgovernment such as carrying out a form of supervision based on community reports andsupervision on its own initiative from the Ombudsman. In addition, the Ombudsman Representativefor Lampung Province conducted socialization with the people of Bandar Lampung City, builtcoordination, and collaboration between institutions and network development in the work area ofBandar Lampung City, this was done to prevent maladministration actions that were rife in BandarLampung City. The people of Bandar Lampung City indicated that the Ombudsman had carried outhis duties as a supervisory agency even though there were people who were dissatisfied with the resultsof the Ombudsman's follow-up. Keywords: Supervision; Ombudsman: Public Service